Effectiveness of technology‐enhanced learning in Endodontic education: a systematic review and meta‐analysis. (10th September 2018) - Nagendrababu, V.; Pulikkotil, S. J.; Sultan, O. S.; Jayaraman, J.; Soh, J. A.; Dummer, P. M. H.
Abstract: The aim of the present systematic review was to evaluate the effectiveness of technology‐enhanced learning (TEL) in the field of Endodontics to improve educational outcomes compared to traditional learning methods. Randomized controlled studies published in English were identified from two electronic databases (PubMed and Scopus) up to May 2018. Two authors independently performed study selection, data extraction and assessed the risk of bias (ROB). Any teaching method using TEL was considered as the intervention, and this was compared to traditional methods. The outcome measuring the effectiveness of learning activities was evaluated by Kirkpatrick's four‐level training evaluation model. The four levels of training outcomes are as follows: Reaction, Learning, Behaviour and Results. A meta‐analysis was performed to estimate the standardized mean difference (SMD) by the random effects model. In total, 13 studies were included in the systematic review. Only three studies were assessed as 'low' ROB. A meta‐analysis could not be performed in the domains of Reaction and Behaviour. No significant difference was observed in knowledge gain (Learning domain) between TEL and traditional methods (SMD, 0.14 (95% CI −0.10 to 0.39) I 2 = 62.7%). Similarly, no difference was observed in performance (Behaviour domain). A variable response was found in attitude (Reaction domain). From the available evidence, it can be concluded that TEL is equally as effective as traditional learning methods.